2015
DOI: 10.14740/jocmr2098w
|View full text |Cite
|
Sign up to set email alerts
|

Serum Survivin Increases in Prolactinoma

Abstract: BackgroundProlactinoma is the most common adult pituitary adenoma. Survivin is a member of the family of inhibitors of apoptosis proteins. Its expression is observed in many tumors. Survivin expression has shown in prolactinoma tissue before but no study exists showing serum survivin level. The aim of the present study was to investigate serum survivin levels in patients with prolactinoma and demonstrate its value in diagnosis of the disease.MethodsThe group of patients consisted of 25 women, aged from 17 to 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In the study by Goricar et al (46) surviving showed level od 4.1 pg/mL at diagnosis, but patients with progressive disease had significantly higher surviving levels before chemotherapy which is in accordance to our results. Other study has also confirmed that surviving level in the advanced stage of different carcinoma locations hits higher levels (49, 50, 51). These deviations in serum levels can be explained by the fact that there are many specificities about tumors that can affect the serum levels of this protein.…”
Section: Discussionmentioning
confidence: 58%
“…In the study by Goricar et al (46) surviving showed level od 4.1 pg/mL at diagnosis, but patients with progressive disease had significantly higher surviving levels before chemotherapy which is in accordance to our results. Other study has also confirmed that surviving level in the advanced stage of different carcinoma locations hits higher levels (49, 50, 51). These deviations in serum levels can be explained by the fact that there are many specificities about tumors that can affect the serum levels of this protein.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported that BIRC5 was overexpression in more than half of breast cancer patients ( Yie et al, 2006 ). In addition to breast cancer, BIRC5 expression has been associated with prognosis and diagnosis of multiple other human cancers such as acute lymphoblastic leukemia ( Ahmed et al, 2012 ), prolactinoma ( Dellal et al, 2015 ), pancreatic cancer ( Dong et al, 2015 ) and non-small cell lung cancer ( Chen et al, 2010 ). On the other hand, BIRC5 overexpression is related to adverse outcome in breast, lung, colorectal, prostate, and ovarian cancer and is thought to be a promising cancer diagnostic biomarker ( Duffy et al, 2007 ; Fawzy et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given that aripiprazole, another atypical antipsychotic drug, similarly reduces the expression of survivin in cancer cells as we demonstrated earlier (11), target receptors shared by olanzapine and aripiprazole may be involved in the regulation of survivin expression. In this regard, it might be interesting to note that serum survivin levels were found to be elevated in prolactinoma patients treated with dopamine D 2 receptor agonists (bromocriptine or cabergoline) in a recent study (35). Although it was not definitively shown in the study whether the increase in serum survivin levels was attributable to the D 2 agonists, the finding may give rise to the intriguing hypothesis that the D 2 receptor pathway plays a role in survivin expression and that olanzapine and aripiprazole inhibit survivin expression through their actions on the D 2 receptor.…”
Section: Discussionmentioning
confidence: 99%